Design and comparison of 14 GHz flip-flop-based frequency dividers in sub-micron CMOS technology - Leong, Zhen Hong (Nanyang Technological University, 2023)
High speed and low power designs are desirable for newer Wi-Fi technologies that are to be implemented in mobile devices. Frequency dividers are essential in many RF circuits and contributes to a large percentage of the total power consumption. This paper reviews various divide-by-two flip-flop-based frequency dividers designed using sub-micron CMOS technology for operation at 14 GHz. The Windmill and Liempd dividers are promising circuits that generate desirable quadrature outputs with good phase noise of less than −145 dBc/Hz while consuming current of less than 800 μA.